1995
DOI: 10.1007/bf00127429
|View full text |Cite
|
Sign up to set email alerts
|

Production of gamma-linolenic acid by Mucor circinelloides and Mucor rouxii with acetic acid as carbon substrate

Abstract: University of the Ormgc Free St&-, PO. 80-v 339, 9300 l~lorn~fontein, South .4frica SUMMARYThe production of gamma-linolenic acid (GLA) by h41rcor circimlloides CBS 203.28 and MI rot/xii CBS 416.77 in fed-batch cultures operated in pH-stat mode with acetic acid as carbon substrate and titrant compared favourably with the performance of A4. circille//oides in batch culture on glucose. On acetic acid A4. circimlloides accumulated up to 39.8 mg GLA/g biomass, with a crude oil content of 28% containing 91% neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…This is might be due to availability of MCFA in coconut oil, and therefore it shows that M. circinelloides should assimilate the MCFA from the coconut into their cells. Our results are consistent with previous studies showing that fungal cells produce more fungal biomass and total lipids when grown in medium-chain-containing oils [42][43][44]. Based on our results, the highest biomass and lipid productivities were achieved with coconut oil mixed medium (g/L•d), while the maximum MCFA contents in terms of the percentage of CDW were obtained with palm oil mixed medium ( Figure 4C).…”
Section: Synergistic Effect Of the Culture Conditions On Fungal Biomasupporting
confidence: 92%
“…This is might be due to availability of MCFA in coconut oil, and therefore it shows that M. circinelloides should assimilate the MCFA from the coconut into their cells. Our results are consistent with previous studies showing that fungal cells produce more fungal biomass and total lipids when grown in medium-chain-containing oils [42][43][44]. Based on our results, the highest biomass and lipid productivities were achieved with coconut oil mixed medium (g/L•d), while the maximum MCFA contents in terms of the percentage of CDW were obtained with palm oil mixed medium ( Figure 4C).…”
Section: Synergistic Effect Of the Culture Conditions On Fungal Biomasupporting
confidence: 92%
“…Addition of carbon sources under both batch and fed-batch mixotrophic cultivation corresponds to a higher C/N ratio and increased lipid content (15). The effect of different initial acetic acid concentrations (1.0-17.0 g/L) in the fed-batch media on the lipid production by Mucor circinelloides was determined by du Preez et al (22). In agreement with our results, results from du Preez et al (22) showed that higher acetic acid concentrations led to a significant increase in the lipid content of the biomass.…”
Section: Resultssupporting
confidence: 93%
“…The effect of different initial acetic acid concentrations (1.0-17.0 g/L) in the fed-batch media on the lipid production by Mucor circinelloides was determined by du Preez et al (22). In agreement with our results, results from du Preez et al (22) showed that higher acetic acid concentrations led to a significant increase in the lipid content of the biomass. Often, nitrogen limitation and excess carbon source trigger lipid accumulation (23).…”
Section: Resultssupporting
confidence: 93%
“…Some pure or single organic acids were used for the production of polyunsaturated fatty acids and lipids (du Preez et al, 1995;Rodrigues and Pais, 2000;Yahara et al, 2007). du Preez et al, 1996 used a mixture of volatile fatty acids (VFAs) as a sole carbon source for gamma-linolenic acid production and obtained 0.3 g biomass/g VFAs and a lipid yield of less than 9% of the VFAs mixture.…”
Section: Introductionmentioning
confidence: 99%